Trans-Golgi Network-Located AP1 Gamma Adaptins Mediate Dileucine Motif-Directed Vacuolar Targeting in Arabidopsis . Issue 10 (28th October 2014) - Wang, Xiangfeng; Cai, Yi; Wang, Hao; Zeng, Yonglun; Zhuang, Xiaohong; Li, Baiying; Jiang, Liwen
Abstract : This work demonstrates that TGN-located AP1 complex mediates dileucine motif-directed vacuolar targeting via the interaction with this conserved sorting signal in plant cells. The deficiency of the AP1 gamma adaptins, as well as the mutations of the dileucine residues, resulted in the mislocalization of tonoplast proteins containing the dileucine motif. Abstract: Membrane proteins on the tonoplast are indispensible for vacuolar functions in plants. However, how these proteins are transported to the vacuole and how they become separated from plasma membrane proteins remain largely unknown. In this study, we used Arabidopsis thaliana vacuolar ion transporter1 (VIT1) as a reporter to study the mechanisms of tonoplast targeting. We showed that VIT1 reached the tonoplast through a pathway involving the endoplasmic reticulum (ER ), Golgi, trans -Golgi network (TGN ), prevacuolar compartment, and tonoplast. VIT1 contains a putative N-terminal dihydrophobic type ER export signal, and its N terminus has a conserved dileucine motif (E KQTLL ), which is responsible for tonoplast targeting. In vitro peptide binding assays with synthetic VIT1 N terminus identified adaptor protein complex-1 (AP1) subunits that interacted with the dileucine motif. A deficiency of AP1 gamma adaptins in Arabidopsis cells caused relocation of tonoplast proteins containing the dileucine motif, such as VIT1 and inositol transporter1, to the plasma membrane. The dileucine motif also effectively rerouted the plasma membrane protein SCAMP1 to the tonoplast. Together with subcellular localization studies showing that AP1 gamma adaptins localize to the TGN, we propose that the AP1 complex on the TGN mediates tonoplast targeting of membrane proteins with the dileucine motif.